Bancassurance Alam Perjanjian Kredit dengan Hak Jaminan Fidusia - A.A Made Andika Purnama Arta; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Jurnal Konstruksi Hukum, 2022)
Bancassurance is a form of cooperation between insurance companies and banks, where the bank here acts as an intermediary between the insurance company and its customers in insurance activities. One type of material guarantee is a fiduciary guarantee. This study aims to find out how the bancassurance legal arrangements so that banks are allowed to carry out credit agreement activities with fiduciary guarantee rights, how the legal consequences of bancassurance in credit agreements with fiduciary guarantee rights, the method used in this study is juridical normative. While the problem approach used is a statutory approach and a conceptual approach. The approach to sources of legal materials used in this research is primary, secondary, and tertiary with analysis of legal materials using legal arguments whose results are presented descriptively. The conclusion is that in the Law of the Republic of Indonesia Number 10 of 1998 concerning amendments to Law Number 7 of 1992 concerning banking, Article 10 (b) of the Banking Law clearly stipulates that Banks may not conduct insurance business.